2015
DOI: 10.1007/s11079-015-9372-x
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Behavior of Canada, Japan, the United Kingdom and the United States

Abstract: We revisit a significant research topic on exchange rate behavior by restating the test procedures with an appropriate econometric methodology to re-examine three aspects. (i) Does the inflation (price) factor affect nominal exchange rate? (ii) Do relative interest rates affect a country's exchange rate? (iii) Do the price and interest rate effects hold if controls for non-parity factors are embedded in tests? The quarterly data series for this study are taken over 55 years. The traditional parity condition mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…I used the variance decomposition analysis based on PVAR 1 model to determine the degree of importance of each variable included in the model. Table 1 shows that exchange rate volatility in PVAR 1 was of great importance for understanding the variations over the 36-month period, parallel to [9,21], implying that the PPP theory may be consistent. FEVDs revealed that changes in economic activity play an important role in the variations in exchange rate volatility in contrast to [5].…”
Section: Variance Decomposition Analysis Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…I used the variance decomposition analysis based on PVAR 1 model to determine the degree of importance of each variable included in the model. Table 1 shows that exchange rate volatility in PVAR 1 was of great importance for understanding the variations over the 36-month period, parallel to [9,21], implying that the PPP theory may be consistent. FEVDs revealed that changes in economic activity play an important role in the variations in exchange rate volatility in contrast to [5].…”
Section: Variance Decomposition Analysis Resultsmentioning
confidence: 99%
“…Factors affecting foreign exchange rates may depend on the level of development of countries, as well as on monetary and non-monetary factors. In other words, nominal and real factors can have considerable amount of impact on exchange rate volatility; the study by [9] can be regarded as a pioneering approach in that extent. [9] extended the traditional parity condition model by including non-parity factors, namely, trade, productivity and foreign reserves using panel techniques for quarterly data series over 55 years.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations